Sentimen Bisnis dan Konsumen dalam Siklus Ekonomi Indonesia - Taufik Akbar; Edi Murdiyanto; Anita Sumelvia Dewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
This research aims to find out the relationship between consumer confidence, business confidence, consumer price index, and composite stock price index in Indonesia because the indicator describes a country's economic cycle as a result of sentiment that occurs. Quantitative descriptive research using multivariate methods of cointegration and granger causality within the VECM statistical framework. The period of the study is from 2015 – 2020. VECM estimation shows that in the long term there is a positive relationship pattern between CCI and itself. Then PMI shows a pattern of positive relationships, while CPI and JCI show negative relationships. Only PMI variables have a significant effect on the CCI in the long run. Then in the short term, PMI has a positive relationship pattern and has a significant influence on CCI and JCI in lags 1 and 2, and has a significant influence on CPI in lag 2. JCI has a positive and significant relationship pattern to CCI and CPI in lag 2. This research still does not discuss the dynamic behavior of the VECM model through the response of each variable to the shock of other variables and forecasting how the response of a variable in the future if a shock occurs in other variables. Governments and central banks must be able to reduce market panic and build a level of public trust. It can be said that optimism from the point of view of the business world and consumers needs to be maintained by stakeholders, especially governments and central banks.